PENGARUH PELAYANAN MUDLARABAH TERHADAP TINGKAT KEPUASAN ANGGOTA KOPERASI DAN MASYARAKAT KOPERASI BHAKTI PERTIWI ABADI JAKARTA TIMUR - Abdullah Fathoni (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
Syaria economy is part of global industry. Every country in the world has a different background in establishing the country, for instances different values, differences in natural resources, and others. For this reason, the approach used to elaborate each of the problems will be different because different country has different methods to face the economic globalization. Compromising the rationality of the cooperative economic thoughts and the sharia economics is a method to find a new balance point between local wisdom, national ideals, and the values of the Indonesian nation in responding to economic globalization. There are two approaches used in this paper. Firstly,